Flax (Linum usitatissimum L.) Fibers for Composite Reinforcement: Exploring the Link Between Plant Growth, Cell Walls Development, and Fiber Properties - Goudenhooft, Camille; Bourmaud, Alain; Baley, Christophe (Frontiers in Plant Science, 2019)
Due to the combination of high mechanical performances and plant-based origin, flax fibers are interesting reinforcement for environmentally friendly composite materials. An increasing amount of research articles and reviews focuses on the processing and properties of flax-based products, without taking into account the original key role of flax fibers, namely reinforcement elements of the flax stem (Linum usitatissimum L). The ontogeny of the plant, scattering of fiber properties along the plant or the plant growth conditions are rarely considered. Conversely, exploring the development of flax fibers and parameters influencing the plant mechanical properties (at the whole plant or fiber scale) could be an interesting way to control and/or optimize fiber performances, and to a greater extent, flax fiber-based products. The first part of the present review synthesized the general knowledge about the growth stages of flax plants and the internal organization of the stem biological tissues. Additionally, key findings regarding the development of its fibers, from elongation to thickening, are reviewed to offer a piece of explanation of the uncommon morphological properties of flax fibers. Then, the slenderness of flax is illustrated by comparison of data given in scientific research on herbaceous plants and woody ones. In the second section, a state of the art of the varietal selection of several main industrial crops is given. This section includes the different selection criteria as well as an overview of their impact on plant characteristics. A particular interest is given to the lodging resistance and the understanding of this undesired phenomenon. The third section reviews the influence of the cultural conditions, including seedling rate and its relation with the wind in a plant canopy, as well as the impact of main tropisms (namely thigmotropism, seismotropism and gravitropism) on the stem and fiber characteristics. This section illustrates the mechanisms of plant adaptation, and how the environment can modify the plant biomechanical properties. Finally, this review asks botanists, breeders and farmers’ knowledge toward the selection of potential flax varieties dedicated to composite applications, through optimized fiber performances. Both fibres morphology and mechanical properties are discussed, in link with their use for composite reinforcement.